2022
DOI: 10.1016/j.celrep.2021.110282
|View full text |Cite
|
Sign up to set email alerts
|

A bidirectional competitive interaction between circHomer1 and Homer1b within the orbitofrontal cortex regulates reversal learning

Abstract: Although circular RNAs (circRNAs) are enriched in the brain, their relevance for brain function and psychiatric disorders is poorly understood. Here, we show that circHomer1 is inversely associated with relative HOM-ER1B mRNA isoform levels in both the orbitofrontal cortex (OFC) and stem-cell-derived neuronal cultures of subjects with psychiatric disorders. We further demonstrate that in vivo circHomer1 knockdown (KD) within the OFC can inhibit the synaptic expression of Homer1b mRNA. Furthermore, we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(72 citation statements)
references
References 74 publications
3
69
0
Order By: Relevance
“…Regarding neuronal ring properties at baseline, we found that, although baseline (pre-choice) ring rate is dynamic across reversal learning, the profound reduction in baseline ring rate of circHomer1 KD neurons during chance reversal may be detrimental to learning at this stage and represent an altered homeostatic response to network activity [80]. Homer1 isoforms are well-known for their activity-regulated homeostatic reorganization of the postsynaptic neuron [18] , and this work reinforces the idea that circHomer1 may be in uencing linear Homer1 isoform localization at the synapse [31] in response to increased network demands required for e cient learning.…”
Section: Low Expression Of Circhomer1 In Rodent Ofc Induces Psychiatr...supporting
confidence: 73%
See 3 more Smart Citations
“…Regarding neuronal ring properties at baseline, we found that, although baseline (pre-choice) ring rate is dynamic across reversal learning, the profound reduction in baseline ring rate of circHomer1 KD neurons during chance reversal may be detrimental to learning at this stage and represent an altered homeostatic response to network activity [80]. Homer1 isoforms are well-known for their activity-regulated homeostatic reorganization of the postsynaptic neuron [18] , and this work reinforces the idea that circHomer1 may be in uencing linear Homer1 isoform localization at the synapse [31] in response to increased network demands required for e cient learning.…”
Section: Low Expression Of Circhomer1 In Rodent Ofc Induces Psychiatr...supporting
confidence: 73%
“…While there is a degree of overlap in circHomer1 expression in patients and controls [31,32] as well as in our animal model [32] (and current work), its expression may be more predictive of a particular behavioral phenotype such as behavioral in exibility that spans multiple disorders rather than any speci c disease as a whole. We present ndings that suggest circHomer1 in uences neuronal signaling and coordination within the OFC during speci c windows critical for e cient learning.…”
Section: Circhomer1 Maintains Cellular Ring Potentialmentioning
confidence: 69%
See 2 more Smart Citations
“…RNA interaction has recently gained popularity as a research topic. Currently, circRNA have also been shown to possesses the ability to interact with speci c mRNA and affected them stability, which in turn regulates tumorigenesis and development [33,34]. However, the important role of circRNA that bind to speci c mRNA in HCC is largely unknown.…”
Section: Discussionmentioning
confidence: 99%